Does the Child Penalty Strike Twice, and If So Why? - Mette Gørtz; Sarah Sander; Almudena Sevilla (Institute of Labor Economics (IZA), 2023)
This paper compares the labor market impact of grandparents before and after the arrival of the first grandchild. We show that grandmothers' labor market outcomes decline more steeply than grandfathers' after the first grandchild's arrival, leading to a 4-10 percent gender earnings gap 5-10 years later. The child penalty is shifted across generations to grandmothers with low education, but daycare availability only affects child penalties. Gender biases towards older women's work are a contributing factor to the disparity in earnings between grandmothers and grandfathers after the arrival of the first grandchild.
Keywords: J13; J14; J16; J22; 330; grandchildren; female labor supply; gender; inequality; retirement